Estudio de impactos ambientales para el desarrollo turístico en el cantón Quevedo, año 2020 - Rodríguez del Rosario, Mayra Rocío (2021)
Tourism is an activity that over time has grown considerably as an industry that contributes to the national and international economy by generating employment and income in a country or locality; However, it depends a lot on the natural environment which generates concern nowadays because the ecosystem is greatly affected by the misuse of natural resources, so much so that with the passage of time several species of animal and plant is becoming extinct in the world and the degradation of the ecosystem is increasing every day, This is due to the high volume of polluting waste that is discarded without prior management, deforestation, accumulation of greenhouse gases, lack of drinking water sources, waste in rivers and estuaries, and electronic waste pollution among others are the main triggers for this to happen. This situation has a negative impact on the tourism development of any country or locality. The main objective of this research is to study the environmental impact on tourism development in the canton of Quevedo, province of Los Rios.